Tingkat Kepercayaan Khalayak terhadap Pemberitaan di Media Massa di Kota Bogor (Pengembangan Media Literasi Pada Khalayak) - Feri Ferdinan Alamsyah; Diana Amaliasari; Imani Satriani (Institut Pertanian Bogor, 2018)
The magnitude of the influence of the dissemination of information in the mass media to the audience, makes the audience should be accustomed to doing media literacy. In the concept of media literacy, a good culture of media is to look at aspects of the level of public trust in information in the mass media. The purpose of this study is to determine the level of public confidence in the news in the mass media. This study uses descriptive quantitative correlational methods. The population in this study were students who enrolled in the city of Bogor, determining the sample using incidental sampling techniques. Khalayak agreed (76.9 percent) that they knew new information from the mass media. By receiving information from the mass media, respondents can add insight related to information displayed in the mass media. On the other hand, the more they receive a lot of information from the mass media, the respondents understand if the news displayed in the mass media is not always objective, some of which benefit certain parties. Therefore, respondents felt the need to know the same news in different mass media. A total of 54.4 percent agreed that respondents believed more in the information conveyed by mass media than social media.